Chemical Method of Receipt of Powder-Like Mixtures of Copper Crystals (Cu) -Nano, Micro Dispersion of for Reinforcement of Polymeric Compositions are Used as Materials for Printing 3D - Gorenko М.V. (Physics and Chemistry of Solid State, 2016)
We consider possibility of the chemical process of obtaining crystals of copper powder mixtures -nano, micro dispersion of for reinforcement of polymeric compositions are used as materials for printing 3D thermo-extrusion method, is given determination the physic and to mechanical properties of the resulting material, depending on the filler, we offer a method to reduce the porosity of products for the SLS technology, DMLS,investigated kinds of crystal structures of copper (Cu) and crystallization process copper (Cu) with -nano phase in solution H2O.